PROTEIN SPECTRUM PRODUCED BY THE DERMAL FIBROBLASTS IN CHILDREN WITH CROHN'S DISEASE - V. S. Kropotov; S. A. Kolesov; E. А. Vasil'eva; I. V. Mayanskaya; V. I. Ashkinazi ("Paediatrician" Publishers LLC, 2013)
The results of the study on production of the protein spectrum by the dermal fibroblasts in relatively healthy children and children with Crohn's disease during consecutive passages are shown in this article. Aim: to establish characteristics of protein spectrum of supernatants derived from the repeated cultivation of fibroblasts under normal and pathological conditions. Patients and methods: supernatants of 4 fibroblast cultures obtained from cutaneous tissue samples of 2 relatively healthy and 2 children with Crohn's diseases aged from 14 to 17 years old were examined. The assessment of protein spectrum was performed by time-of-flight mass spectrometry MALDI-TOF (Bruker Autoflex, USA); phenotyping was performed by flaw cytometry assay (FACS Cantu II, USA). Results: 5 clusters of protein distribution according to the molecular weight were distinguished by the methods of statistical analysis:  from 0,8 to 3,3 kDa, from 3,3 to 6,0 kDa, from 6,0 to 11,0 kDa, from 11,0 to 16,6 kDa and >16,6 kDa. Proteinograms of patients with Crohn's disease and relatively healthy children differ from each other. Conclusions: certain special features of proteomic profile, characterizing supernatants of fibroblastic cultures of children with Crohn's disease were found. The established characteristics of proteomic spectrum of fibroblast secretory components can be used as marker of their activity at different stages of cultivation.